2001
DOI: 10.1034/j.1399-3054.2001.1120213.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo sucrose stimulation of colour change in citrus fruit epicarps: Interactions between nutritional and hormonal signals

Abstract: During ripening, citrus fruit-peel undergoes 'colour break', a process characterized by the conversion of chloroplast to chromoplast. The process involves the progressive loss of chlorophylls and the gain of carotenoids, changing peel colour from green to orange. In the present work, the in vivo and in vitro effects of supplemented nutrients (sucrose and nitrogen) and phytohormones (gibberellins [GA] and ethylene) on colour change in fruit epicarp of Satsuma mandarin (Citrus unshiu (Mak.) Marc., cv. Okitsu), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
2
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 28 publications
5
99
2
5
Order By: Relevance
“…Based on data collected from in vitro studies on citrus epicarp, Huff (1983Huff ( , 1984 suggested that citrus fruit might partially de-green in response to the accumulation of sugars. It has specifically been shown that the chloroto chromoplast conversion in citrus fruit epicarps is stimulated by sucrose accumulation after an initial decrease in peel nitrogen content (Iglesias et al, 2001). In this work it is proposed that sugar regulation may operate via ethylene, whereas GA functions as a repressor of the ethylene-sucrose stimulation.…”
Section: External Ripeningmentioning
confidence: 82%
See 1 more Smart Citation
“…Based on data collected from in vitro studies on citrus epicarp, Huff (1983Huff ( , 1984 suggested that citrus fruit might partially de-green in response to the accumulation of sugars. It has specifically been shown that the chloroto chromoplast conversion in citrus fruit epicarps is stimulated by sucrose accumulation after an initial decrease in peel nitrogen content (Iglesias et al, 2001). In this work it is proposed that sugar regulation may operate via ethylene, whereas GA functions as a repressor of the ethylene-sucrose stimulation.…”
Section: External Ripeningmentioning
confidence: 82%
“…The changes associated with external ripening are essentially comparable to the senescence of vegetative chlorophyllous tissues and in citrus fruits are influenced by environmental conditions, nutrient availability and hormones (Goldschmidt, 1988;Iglesias et al, 2001). Color break in subtropical areas generally takes place in midautumn when temperatures go down and day length diminishes (Figure 4).…”
Section: External Ripeningmentioning
confidence: 99%
“…Embora seus frutos sejam semelhantes às da laranja Pera, possivelmente apresenta maturação mais precoce, já que de acordo comacordo com Schinor et al (2010) A coloração é o atributo de qualidade mais atrativo para o consumidor, sendo um dos fatores determinantes na aquisição dos frutos, pois é associada com a maturação, frescor e também com o sabor. A cor externa dos frutos cítricos é o parâmetro fundamental para o mercado de frutos frescos, pois o consumidor prefere frutas semimaduras, para prolongar o período de durabilidade, além de julgar a fruta verde de forma negativa (EDAGI et al, 2010;IGLESIAS et al, 2001;BADENES et al, 1998).…”
Section: Resultsunclassified
“…El proceso de desverdizado natural se puede modificar con aplicaciones exógenas de reguladores de crecimiento, tales como ácido giberélico (Goldschmidt y Eilati, 1970, Kuraoka et al, 1977 y etileno (Pons et al, 1992;Goldschmidt et al, 1993); sustancias nitrogenadas (Jones y Embleton, 1959;Sala et al, 1992;Quiñones et al, 2004) y carbohidratos (Iglesias et al, 2001). …”
Section: Discussionunclassified
“…La sacarosa se incrementó hasta el inicio del cambio de color de los frutos y, posteriormente, se mantuvo relativamente estable, con pequeñas variaciones entre cultivares, lo que sugiere que a partir de ese momento el aumento de los restantes azúcares es producto de su hidrólisis. Se ha señalado que el suplemento de sacarosa in vitro (Huff, 1983) o in vivo (Iglesias et al, 2001) promueve el desverdizado del flavedo de los cítricos.…”
Section: Discussionunclassified